SEASONAL VARIATION OF THE FOLIAR CONSTITUENTS OF PRIMARY (MACHILUS BOMBYCINA) AND SECONDARY (LITSEA CITRATA) FOOD PLANTS OF ANTHERAEA ASSAMENSIS HELFER (MUGA SILKWORM) IN NAGALAND - B. T. KAKATI,; L. N. KAKATI,; B. C. CHUTIA, (The Bioscan, 2015)
Seasonal variation of certain foliar constituents of Machilus bombycina King (Som) and Litsea citrata Blume (Mejankori), the primary and secondary food plants respectively of Antheraea assamensis Helfer (muga silk worm) were estimated in Nagaland. The moisture and total carbohydrate were recorded to be maximum during summer season both in Som (69.81±0.34% and 10.48±0.54%) and Mejankori (68.59±0.60% and 14.16±0.39%) respectively. The mean value of moisture was higher in Som (67.66±0.49%) than Mejankori (65.18±0.91%) leaves while the reverse was observed in case of total carbohydrate (9.82±0.24% and 12.52±0.42% respectively). The crude fibre was recorded maximum during spring in both Som (17.38±1.28%) and Mejankori (20.18±1.76%) with fluctuating trend during summer and winter season. The total nitrogen, crude protein and total ash were higher in Som (3.15±0.06%, 19.66±0.35% and 8.10±0.19% respectively) during spring season, while Mejankori retained higher percentage of these constituents (3.01±0.12%, 18.82±0.74% and 4.11±0.09% respectively) during winter season. The soluble and reducing sugar in Mejankori (4.80±0.29% and 0.39±0.06%) and Som (3.73±0.29% and 1.43±0.12%) was recorded maximum during summer and winter respectively. The mean total soluble sugar content was found to be higher in Mejankori (3.78±0.28%) than Som (3.32±0.13 %) whereas the total reducing sugar content was found to be higher in Som (1.39±0.06%) than Mejankori (0.32±0.03%). Interaction effect between seasons and food plants revealed significant differences for moisture, total carbohydrate, soluble sugar, total nitrogen and crude protein while difference were insignificant for reducing sugar, crude fibre and total ash.